Case Report: Fulminant Myocarditis Successfully Treated With Extracorporeal Membrane Oxygenation in Ikeda Strain Orientia tsutsugamushi Infection - Park, Hyejin; Lim, Yongwhan; Kim, Min Chul; Kim, Seong Eun; Jeong, In-Seok; Choi, Yoo Duk; Kim, Dong-Min (Frontiers in Cardiovascular Medicine, 2021)
Scrub typhus is an acute zoonotic febrile illness caused by Orientia tsutsugamushi having specific geographic endemic area. This infection could be complicated with multi-organ involvement including myocarditis with variable severity. Here, we report a rare case of scrub typhus with biopsy-proven acute fulminant myocarditis which progressed very rapidly to cardiac arrest and treated successfully with extracorporeal cardiopulmonary resuscitation. Clinicians should be alert to possible rapid progression of scrub typhus myocarditis to fulminant form and be prepared for close monitoring and temporary mechanical support if indicated.